Conveyor Belt Furnace Thermal Processing - Xu, Jinlong (Springer International Publishing, 2018)
Distills more than a decade's worth of application experience on furnaces into a practical book for engineers; Addresses belt furnace influences on manufacturing, assembly and packaging, efficiency, curing, and more; Focuses on lithium ion batteries, direct bond copper technologies, and solar cells. This practical book is tailored for engineers working in the industry, and condenses more than a decade's worth of application experience on furnaces. The various topics discussed include conveyor furnaces, belt furnaces, solar cells, brazing furnaces, thick film furnaces, and furnace air flow and reflow. There are chapters on the influence of belt furnace and firing on silicon solar cells, thin film CIGS solar cells, dye-sensitized solar cells, crystalline solar cells, and lithium ion batteries, as well as how the processes affect the efficiency of each. The authors also address the influence of belt furnace on various processes such as metallization, engine valve heat treatment, brazing, post mold curing, and glass-to-metal sealing. The last few chapters also address Direct Bond Copper (DBC) technologies, and the effect of profile and atmosphere on the reflow process.